2021
DOI: 10.1016/j.mayocp.2021.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status Is Associated With In-Hospital Mortality and Mechanical Ventilation: A Cohort of COVID-19 Hospitalized Patients

Abstract: Objective: To explore the possible associations of serum 25-hydroxyvitamin D [25(OH)D] concentration with coronavirus disease 2019 in-hospital mortality and need for invasive mechanical ventilation. Patients and Methods: A retrospective, observational, cohort study was conducted at 2 tertiary academic medical centers in Boston and New York. Eligible participants were hospitalized adult patients with laboratory-confirmed COVID-19 between February 1, 2020, and May 15, 2020. Demographic and clinical characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 39 publications
2
51
1
13
Order By: Relevance
“…We have clearly demonstrated that vitamin D insufficiency and deficiency exponentially increase the risk of the disease by a factor of 2.3 to 3.6, even after adjustments for age and sex. However, we did not find any association between low 25(OH)D levels or vitamin D status and excess mortality risk, as observed in previous studies ( 6 , 8 , 11 , 12 ).…”
Section: Discussionsupporting
confidence: 66%
“…We have clearly demonstrated that vitamin D insufficiency and deficiency exponentially increase the risk of the disease by a factor of 2.3 to 3.6, even after adjustments for age and sex. However, we did not find any association between low 25(OH)D levels or vitamin D status and excess mortality risk, as observed in previous studies ( 6 , 8 , 11 , 12 ).…”
Section: Discussionsupporting
confidence: 66%
“…Quando se trata do uso de ventilação mecânica ou comprometimento pulmonar em comparação aos baixos níveis de 25(OH)D nos pacientes com COVID-19, evidenciou-se uma ausência de relação positiva em ambos os casos (Angelidi et al, 2021;Orchard et al, 2021;Reis et al, 2021;Pizzini et al, 2020)…”
Section: Resultsunclassified
“…Verifica-se que a maioria dos estudos observacionais analisados apresentou associação da deficiência de vitamina D e COVID-19 com diferentes perspectivas e desfechos. Em relação a mortalidade,Angelidi et al (2021), De Smet et al (2021), Karahan Katkat (2021), Orchard et al (2021), Reis et al (2021) e Sulli et al (2021) não mostraram associação significativa quando comparados com as concentrações séricas de 25(OH)D. No entanto, Alcala-Diaz et al (2021), Alsafar et al (2021), Carpagnano et al (2021) e Vassiliou et al (2020) relataram que pacientes com deficiência grave de 25(OH)D possuíram maior risco de mortalidade por COVID-19, principalmente, quando comparados àqueles com maiores concentrações de 25(OH)D.…”
unclassified
“…25(OH) vit. D level was reported in ng/ml, which can be multiplied by 2.496 to be converted to nmol/l [14].…”
Section: Methodsmentioning
confidence: 99%